Legal Counseling On Civil Rights Due To Marriage Different Religions In Ogan Ilir Regency – South Sumatra Province - Junaidi; Mila Surahmi; Desmawaty Romli; Citra Dewi Saputra; Liza Nofianti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2021)
Interfaith marriage is a marriage bond between a man and a woman who have different beliefs and religions. In principle, interfaith marriages are prohibited by every religious teaching. Every religious instruction requires a marriage bond to be carried out in a bond of the same faith (one religion). Based on Article 2 paragraph (1) of Law Number 1 of 1974 concerning Marriage, it is explained that a marriage is considered valid if it is carried out according to their respective religions and beliefs. Legal problems arise due to interfaith marriages, including the validity of marriages that give rise to rights and obligations between husband and wife and children's status due to interfaith marriages on their inheritance rights. Interfaith marriages occur in society but are usually covered up. In the case of interfaith marriages in Ogan Ilir Regency, our Community Service Team, Faculty of Law, Sjakhyakirti University conducted legal counseling to understand the legal consequences of interfaith marriages, especially regarding the validity of marriages, child status, and inheritance.